Chemical reactions of a CL-20 crystal under heat and shock determined by ReaxFF reactive molecular dynamics simulations. Issue 40 (9th October 2020) - Wang, Fuping; Chen, Lang; Geng, Deshen; Lu, Jianying; Wu, Junying
Abstract : For the first time, different chemical reactions of CL-20 under heat and shock were studied using ReaxFF reactive molecular dynamics. Abstract : Studying the chemical reactions of hexanitrohexaazaisowurtzitane (CL-20) under heat and shock is helpful to understand its sensitivity and shock initiation mechanism. In this work, several molecular dynamics simulations were performed under three different conditions: high temperature, high temperature and pressure, and shock. The formation and breakage of chemical bonds, changes of bond lengths, and initial reactions were analysed. It was found that the main small-molecule product of CL-20 during initial decomposition under the three different conditions was always NO2, but the generation pathways were different. At high temperatures, NO2 was generated by the direct cleavage of N–NO2 bonds. In contrast, high pressure and shock promoted the transfer of O atoms to N atoms connected to NO2, leading to the breakage of N–NO2 bonds. Almost all NO2 originated from the transfer of O atoms under the shock conditions.